Leadership and authority : - edited by Gehan Wijeyewardene. (Published for the Centre for Southeast Asian Studies in the Social Sciences, University of Singapore, by the University of Malaya Press, 1968)
Proceedings of a symposium held at the University of Singapore, December 8-13, 1963.